DEVELOPING THE RESOLUTIONS FOR THE ELECTRONIC WASTE PROBLEM: A CASE STUDY OF KHOK SA-AD, KHONG CHAI, KALASIN - Pimon, Supaporn; Zumitzavan, Vissanu (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were to suggest the solutions to electronic waste problems in Khok Sa - ad Subdistrict, Khong Chai District, Kalasin Province from the hidden dangers of electronic waste. This research applied a qualitative method from in - depth interviews using semi - structured interview questions to collect information. Pre - interview questions were created in the data collection stage with fieldwork. The pilot study questions were tested to develop questions and verify their level of validity and reliability. Sampling was selected using purposive sampling from stakeholders aged 20 years and over who have expertise in e - waste or having an occupation in sorting e - waste for at least 10 years and local government officials in the area. The informants consisted of 14 people and staff in Khok Sa - ad Subdistrict Administrative Organization. The interview began during November - December 2020, which was an informal interview. The questions were prepared before the interview. There was a use of recording equipment and taking notes of the interview data. The results of the research showed that solving the problems should seriously involve the public and raise awareness among the people, which will lead to more quality problem solving and reduce the impact that may occur in the future. The occupation of sorting electronic waste in the area has a low level of public participation and people still lack awareness of the dangers of electronic waste. The operation does not take health and the environment into consideration for the community.